Can E-Commerce Policies Drive Common Wealth Levels —— A Study Based on County-Level Data in China, 2012-2020 - Guo, Guanlin (Transactions on Economics, Business and Management Research, 2024)
Based on national county panel data from 2012 to 2020, this study systematically examines the impact of the comprehensive e-commerce into rural areas demonstration project implemented in rural China on promoting the level of common wealth by applying the multi-period double-difference method (DID). It is found that the e-commerce policy significantly enhances the level of common wealth. Further analysis of the impact mechanism shows that the policy effectively promotes the goal of common prosperity by enhancing the level of rural employment. In addition, the positive effect of the e-commerce policy is strengthened by the increase in the level of local government fiscal expenditure, however, the driving effect of the policy is weakened by the higher level of social consumption. Heterogeneity analyses indicate that the policy's promotional effect is particularly significant in the demonstration counties of the Yangtze River Economic Belt. This paper fills the research gap on the relationship between rural e-commerce policy and the level of common wealth, and provides empirical evidence and policy recommendations for related policy formulation.